The mediatization of a Latin American agro-city. Television consumption inside and outside households - Carniglia, Edgardo Luis (2019)
The interrelationship between the modern processes of urbanization and mediatization is a sociocultural key of Latin America in the 21st century. The mediatization of everyday life, expressed herein through the consumption of television, crosses different urban spaces: megalopolises, large cities, medium-sized cities and small towns. In particular, this text shows how television consumption is also deployed in a scenario of digital transition, the agro-city of Argentina, a specific hybrid territory made up of the integration of urban and rural features. This study includes three operations of a methodological convergence or triangulation strategy: a) the discussion of the background, relevance and significance of the “agro-city” notion within the frame of the sociocultural theory in order to understand its implications on studies about the relationships between communication, media and urban territories; b) the analysis of serial quantitative secondary data on television consumption in the households of a particular urban configuration such as the Río Cuarto town (Córdoba, Argentina); and c) an ethnographic exploration of other places within this medium-sized urban area that describes certain ways of exposure to television also given on a daily basis and outside households.